Efforts to Build Nationalism Values to Vocational High School Students with The implementation of Character Education - Ichsan Ichsan; Hendy Tannady; Arief Nuryana; Tuti Marjan Fuadi; Purniadi Putra (STKIP PGRI SITUBONDO, 2023)
In Indonesia, character education first appeared since 2010 to be implemented at all levels of education, from elementary school to university. This is indicated by the presence of character value content in the Lesson Plan (RPP) and learning syllabus. However, these efforts are considered to have not been able to fully deliver the nation's generation into dignified individuals, because the output of educational graduates produced is only limited to giving birth to a high intellectual level but good character values and personality attitudes have not been seen in the life of the nation and state. This type of research is descriptive qualitative. The research subjects were school principals, deputy heads of student affairs and teachers. The research data were obtained through observation, interviews and documentation. The results of the study show that the organization, implementation, evaluation and follow-up of the implementation of policies to strengthen character education related to efforts to instill nationalism values have been carried out with an integration process through intra-curricular, co-curricular, extra-curricular and school culture activities. Suggestions from this study are to continue to increase the intensity of supervision of the implementation of PPK (Strengthening Character Education), improve the quality of PPK activities in an effort to instill character values in students.